Pensions: global issues, perspectives and challenges - Filipe, J. A. (International Journal of Latest Trends in Finance and Economics Sciences, 2018)
The objective of this work is the book “Pensions: Global Issues, Perspectives and Challenges”, 2017, 978-1-53612-467-5, from Nova Science Publishers Series Business Issues, Competition and Entrepreneurship. The editor is Alexandra Webb.